2007
DOI: 10.1159/000101717
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fecal Incontinence in Children

Abstract: Fecal incontinence is defined as the passage of stools in an inappropriate place. This frustrating symptom is a source of considerable distress and embarrassment for the child and his/her family. Pediatric fecal incontinence can be divided into 2 main categories: (1) organic fecal incontinence, e.g., resulting from anorectal malformations or neurogenic abnormalities, and (2) functional fecal incontinence. This review will only address functional fecal incontinence in children, and the definition, epidemiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…FI is defined as passage of a stool without control (usually in a socially inappropriate place) after 4 years of age, at least once a month over a 3-month period. [1][2][3][4][5][6][7][8][9][10] When first presented, FI may be associated with CC, which causes misguided management, yet studies have shown that over 80% of children with CC also suffer from FI [11][12][13] and thus their coexistence is now universally accepted. FI has an estimated worldwide prevalence in children of up to 8%, 14 with the majority of children having it secondary to CC.…”
Section: Introductionmentioning
confidence: 99%
“…FI is defined as passage of a stool without control (usually in a socially inappropriate place) after 4 years of age, at least once a month over a 3-month period. [1][2][3][4][5][6][7][8][9][10] When first presented, FI may be associated with CC, which causes misguided management, yet studies have shown that over 80% of children with CC also suffer from FI [11][12][13] and thus their coexistence is now universally accepted. FI has an estimated worldwide prevalence in children of up to 8%, 14 with the majority of children having it secondary to CC.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of FI varies from less than 1% to more than 4% in children around the world (2–6). It is more common among boys (7), younger children, and those from lower socioeconomic background (4).…”
mentioning
confidence: 99%
“…FI typically involves diarrhea, impaired bowel storage capacity, and a weakening of the pelvic floor [ 1 , 2 ] ( Table 1 ). FI is usually considered abnormal after about 4 years of age once toilet training has been completed [ 3 ].…”
Section: Definitionmentioning
confidence: 99%